Hussein And Navoi (1438–1506) - Bobonazar Murtazoev (Zien Journals, 2021)
The article analyzes the life of the statesman and poet Hussein Boykaro, the creative collaboration of the leaders of the literary environment of Herat Jami and Navoi.
Keywords: History; king; poet; work